Analisis Integratif Sistem Peradilan Nasional tentang Pelaksanaan Mediasi dalam Kasus Perceraian yang Diajukan oleh Istri di Pengadilan Agama - Putra, Muhammad Zidan Arzaki; Kaha, Humaidi (STIS Ummul Ayman, Pidie Jaya, Aceh, Indonesia, 2025)
Divorce lawsuits filed by wives in Indonesia’s Religious Courts reflect evolving social dynamics and increasing legal awareness among women. Although mediation is mandated by PERMA No. 1 of 2016 and updated by PERMA No. 3 of 2022, its effectiveness in divorce cases remains questionable. This study aims to examine whether the current mediation system ensures substantive justice for women as plaintiffs and to identify the normative and structural challenges that hinder the integration of mediation into the national judicial system. Using a normative-empirical approach, this research analyzes legal norms, empirical data, and the socio-psychological context faced by women who file for divorce. Findings reveal that mediation is often reduced to a formalistic procedure, lacking sensitivity to gender dynamics and failing to provide a safe and equitable space for women. Normative barriers include the absence of gender-responsive regulations, while structural obstacles include insufficient training, lack of qualified mediators, and inadequate facilities. To overcome these challenges, an integrative approach is essential—one that combines legal, psychological, cultural, and gender perspectives. Reform strategies include regulatory revision, gender-based mediator training, multidisciplinary collaboration, and enhanced institutional support. Such reforms are expected to transform mediation into a more effective, fair, and human-centered mechanism for resolving marital disputes initiated by women.